Fuzzy Idealization on \(gb\)-Continuity (Journal of Informatics and Mathematical Sciences, 2017)
In this work, we introduce the notions of \(fgb\)-\(I\)-closed sets, \(fgb\)-\(I\)-continuous, \(fgb\)-\(I\)-irresolute, \(fgb\)-\(I\)-open functions and \(fgb\)\(^*\)-\(I\)-open functions in fuzzy ideal topological spaces and investigate some of their characterizations and properties.
Keywords: \(fgb\)-\(I\)-closed sets; \(fgb\)-\(I\)-neighbourhood; \(fgbq\)-\(I\)-neighbourhood; \(fgb\)-\(I\)-continuous functions; \(fgb\)-\(I\)-irresolute functions; \(fgb\)-\(I\)-closed functions; \(fgb\)\(^*\)-\(I\)-open functions; fuzzy \(gb\)-\(I\)-\(T_{1/2}\